Analysis of enzyme activity, antibacterial activity, antiparasitic activity and physico-chemical stability of skin mucus derived from Amphiprion clarkii. Issue 86 (March 2019) - Wang, Huan; Tang, Wei; Zhang, Rui; Ding, Shaoxiong
Abstract: Recently, mucosal surfaces, especially fish skin and its secreted mucus, have attracted significant interest from immunologists. Amphiprion clarkii, a member of the family Pomacentridae, lives symbiosis with sea anemones and has a good resistance to common seawater bacterial diseases and parasites owing to the protection from its abundant skin mucus. In the present work, the activity of immune-related enzymes (lysozyme, protease, antiprotease, cathepsin B, alkaline phosphatase and peroxidase), the antibacterial activity against two Gram-positive bacteria and five Gram-negative bacteria, the antiparasitic activity against the pathogen of marine white spot disease ( Cryptocaryon irritans theronts) and the physico-chemical stability (to pH and heat) of the skin mucus of A. clarkii were analysed. The results showed that the levels of lysozyme and peroxidase were very similar (from 2 to 4 U mg −1 protein). However, cathepsin B was detected of 63.32 U mg −1 protein and alkaline phosphatase was only 0.12 U mg −1 protein. Moreover, protease showed a higher percentage of activity than antiprotease. A. clarkii skin mucus showed a strong antibacterial activity against Gram-negative bacteria, particularly against Aeromonas hydrophila and Vibrio parahaemolyticus but showed no effect on Gram-positive bacteria at the tested concentrations. The bactericidal activity functioned within a short time in a distinct time- and dose-dependent manner. SEM showed that after treated with A. clarkii skin mucus, the V. parahaemolyticus cells distorted and piled together, and the filaments appeared and became into cotton-shaped or quasi-honeycomb texture to adhere cells. Meanwhile, A. clarkii skin mucus showed an apparent antiparasitic activity against C. irritans theronts with a distinct dose- and time-dependent relationship. LM and SEM observation showed that after treated with skin mucus, the theronts quickly stopped their swimming and cilia movement, cells became rounded, cilia shed, small bubbles formed on the surface, cell nucleolus enlarged, cytoskeleton deformed, cell membranes ruptured and cell content leaked out. Antibacterial activity was not affected by 30–90 °C heat treatment but was slightly suppressed by 100 °C. In the pH treatment groups, antibacterial activity was not affected by the moderate pH treatment of 5.0–8.0, but slightly suppressed by weak acid and weak base. Therefore, we speculated that the skin mucus of A. clarkii might be a potential source of novel antibacterial and antiparasitic components for fish or human health-related applications. This study broadened our understanding of the role of skin mucus in the innate immune system and provided a basis for the further isolation and purification of active substances. Highlights: Several immune-related parameters of the skin mucus of a coral reef fish, Amphiprion clarkii were analysed. Several enzymes showed a lower activity level in A. clarkii than has been reported in most other marine fish. Skin mucus showed a strong bactericidal activity in a distinct time- and dose- dependent manner. Skin mucus showed an apparent antiparasitic activity with a distinct dose- and time-dependent relationship. The antibacterial activity was almost not affected by heat treatment and moderate pH treatment.